Análise da gestão de projetos com ênfase na sua maturidade: uma survey multi-setorial - Herszon Filho, Leon (2004)
Many Brazilian companies have been reaiizing the advantage of managing professionally their projects and start to foilow the best practices from the Project Management Institute (PMI), an international organization dedicated to the professionaiism of project management, founded 011 1969, and with more than 100 thousand members worldwide. The main reason is regarding financial benefits and performance improvement based on these best practices appiication. In the other hand, the analysis of the Estudo de Benchmarking em Gestão de Projetos (EBGP Benchmarking study on project management), conducted in 2003 by the Rio de Janeiro Chapter of PMI, has a tendency to conclude that Brazilian companies can improve a iot their level of maturity in managing their projccts. Dr Harold Kerzner s Project Management Maturity Model was the base of the EBGP. This work presents an analysis of a survey conducted with 60 companies from three different industries: Construction, Ou, Gas and Energy; and Telecommunication and Technoiogy. The main objective of this work is to answer some questions related to the levei of success of the projects managed by these companies, their best practices and methodologies. The result shows our local companies are not mature and that the construction industry is more mature ifcompared with others